RESPON PERTUMBUHAN VEGETATIF TANAMAN KACANG HIJAU (VIGNA RADIATA L.) TERHADAP PENGGUNAAN AIR CUCIAN BERAS DAN PUPUK NPK 16-16-16 DI POLIBAG - Sri Susanti Ningsih; Mirna Wulandari; Syafrizal Hasibuan (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2023)
This research was conducted in Siumbut Baru, Village Kisaran Timur Discrit, Asahan Regency, North Sumatra. This research was conducted in January-February 2023. A factorial randomized block design (RDB) was used to design this study. This first factor is the treatment with rice washing water (A) wich has four lavels, namely A0=0 ml/liter of water per polybag (Control), A1=125 ml/l of water polybag of rice washing water, A2 =250 ml/l liter of water/polybag of rice and A3 = 375 ml/1 liter of water/polybag of Rice Washing Water. The second factor was the NPK 16-16-16 (N) treatment at three levels, namely N0 = 0 g/polybag of NPK 16-16-16 (control), N1 = 0.875 g/polybag of NPK 16-16-16 fertilizer (125 kg /ha), N2 = 1.75 g/polybag (250 kg/ha). The results showed that rice washing water increased plant height 4 weeks after planting when the concentration was 375 ml/1 liter of water/a polybag of rice washing water (A3) was 25.94 cm, the number of leaves increased 4 weeks after planting when the concentration was 375 ml/1 liter of water /polybag of rice washing water (A3) was 29.33 strands, the fastest flowering age when the concentration was 0 ml/1 liter of water/polybag (A0) was 37.28 days. At the age of 4 weeks after planting, treatment of plants with NPK 16-16-16 (N) significantly increased plant height. Plants reached a maximum height of 24.90 cm at a dose of 1.75 g/polybag (N2), and had a maximum number of leaves of 25.08 at the same dose. Rice water and NPK 16-16-16 fertilizer did not change all parameters of green bean plants.